Arsitektur Vernakular Tatar Pasundan dalam Perancangan Pasar Induk - Basuki,; Eghi Dwi Yulianto,; Dwi Istiningsih, (ReTII, 2022)
The development of an area can be seen from various sectors, one of which is the trade sector. In this case the market is an important point for an area because there is an exchange of goods and services. For people, the market has become a part of everyday life, not only as a means of trade but also as a means of social interaction between community groups. Banjar Patroman is a city in the province of West Java, Indonesia. Banjar City is an agricultural city where two thirds of the area is rural with extensive agricultural and plantation land. Therefore, the agricultural and plantation sectors have a role in the economic growth of Banjar City. This condition is not proportional to the development of existing trading facilities. Thus, the main market emerged as a solution to accommodate growing economic activities, especially in the trade and agriculture/plantation sectors. The concept of vernacular architecture was chosen in the design of Main Market which aims to preserve elements or characteristics of local architecture, especially Sundanese architecture which emphasizes the relationship between humans and nature/environment.